2013
DOI: 10.1159/000351409
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Plasma Cell-Free DNA in Predicting Postoperative Recurrence of Clear Cell Renal Cell Carcinoma

Abstract: Background: Circulating cell-free DNA (cfDNA) mostly originates from tumors and its level correlates with treatment. We assessed whether the level of plasma cfDNA could help monitor recurrence after nephrectomy. Methods: This study included 92 patients with clear cell renal cell carcinoma (cRCC). Quantitative real-time PCR was used to measure the level of plasma cfDNA before and after nephrectomy. Results: The pretreatment level of plasma cfDNA in patients with metastatic cRCC (6.04 ± 0.72) was significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 19 publications
0
39
1
2
Order By: Relevance
“…Higher cfDNA levels during the course of treatment also indicated poor prognosis [13]. Another study found that plasma cfDNA levels were elevated in metastatic RCC relative to localized disease and could predict postoperative recurrence with 91% sensitivity and 100% specificity [14]. In bladder cancer, urine cfDNA levels were found to be significantly elevated relative to controls [15].…”
Section: Clinical Applications Of Cell-free Dnamentioning
confidence: 99%
“…Higher cfDNA levels during the course of treatment also indicated poor prognosis [13]. Another study found that plasma cfDNA levels were elevated in metastatic RCC relative to localized disease and could predict postoperative recurrence with 91% sensitivity and 100% specificity [14]. In bladder cancer, urine cfDNA levels were found to be significantly elevated relative to controls [15].…”
Section: Clinical Applications Of Cell-free Dnamentioning
confidence: 99%
“…However, the accurate detection of copy number alterations is still challenging since only a very small fraction of total cfDNA is derived from tumors in most patients. The presence of tumor cell-free DNA in plasma of patients with ccRCC has been shown before [44, 45], therefore we attempted to detect the chromosome aberrations characteristic for ccRCC in patients’ plasma using shallow NGS and WISECONDOR software [46]. In our proof of concept experiment we show cfDNA contains more advanced chromosome aberrations than detected by the genomic SNP array on tumor sample.…”
Section: Discussionmentioning
confidence: 62%
“…Cell-free DNA is shed from apoptotic and necrotic cells into the blood stream ( 66 ). Since its first identification in cancer patients ( 67 ), it has been investigated as both a diagnostic ( 68 , 69 ) and prognostic cancer ( 70 , 71 ) biomarker in RCC and other cancers ( 72–75 ). However, cell-free DNA is not yet clinically validated in RCC.…”
Section: Discussionmentioning
confidence: 99%